Selective inhibitors of bromodomain BD1 and BD2 of BET proteins modulate radiation-induced profibrotic fibroblast responses: cancer therapy and prevention - Liu, Chun-Shan; Rioja, Inmaculada; Bakr, Ali; Veldwijk, Marlon Romano; Sperk, Elena; Herskind, Carsten; Weichenhan, Dieter; Prinjha, Rab K.; Plass, Christoph; Schmezer, Peter; Popanda, Odilia (International journal of cancer, 2022)
Radiotherapy can induce various adverse effects including fibrosis in cancer patients. Radiation-induced aberrant expression of profibrotic genes has been associated with dysregulated epigenetic mechanisms. Pan-BET (bromodomain and extraterminal domain) inhibitors, such as JQ1 and I-BET151, have been reported to attenuate the profibrotic response after irradiation. Despite their profound preclinical efficacy, the clinical utility of pan-inhibitors is limited due to observed cytotoxicicities. Recently, inhibitors were developed that selectively target the first (BD1) and second (BD2) bromodomain of the BET proteins (iBET-BD1 [GSK778] and iBET-BD2 [GSK046]). Here, their potential to attenuate radiation-induced fibroblast activation with low-toxicity was investigated. Our results indicated that cell proliferation and cell cycle progression in fibroblasts from BJ cells and six donors were reduced when treated with I-BET151 and iBET-BD1, but not with iBET-BD2. After irradiation, induction of DGKA and profibrotic markers, especially COL1A1 and ACTA2, was attenuated with all BET inhibitors. H3K27ac enrichment was similar at the DGKA enhancer region after I-BET151 treatment and irradiation, but was reduced at the COL1A1 transcription start site and the ACTA2 enhancer site. iBET-BD2 did not change H3K27ac levels in these regions. BRD4 occupancy at these regions was not altered by any of the compounds. Cell migration activity was measured as a characteristic independent of extracellular matrix production and was unchanged in fibroblasts after irradiation and BET inhibitor-treatment. In conclusion, iBET-BD2 efficiently suppressed radiation-induced expression of DGKA and profibrotic markers without showing cytotoxicity. Thus BD2-selective targeting is a promising new therapeutic avenue for further investigations to prevent or attenuate radiotherapy-induced fibrosis.
Online veröffentlicht: 3. März 2022
Gesehen am 05.12.2023